Effect of Deposited Ammonium Bromide as Flame-Retardant on the Flame-Retardancy Imparted to Cotton Fabric - MORTEZA MOSTASHARI, SAYED; FALLAH MOAFI, HADI (Asian Journal of Chemistry, 2010)
In this work, the effect of ammonium bromide as a nondurable finish on the flammability of 100 % cotton fabric, (woven construction, weighing 160 g/m2) has been investigated. The laundered bone-dried, weighed fabrics were impregnated with suitable concentrations of aqueous ammonium bromide solutions by means of squeeze rolls and dried at 110ºC for 0.5 h. Afterwards they were cooled in a desiccator, reweighed with an analytical precision and kept under ordinary conditions before the fulfillment of the vertical flame test. The optimum add-on values to impart flame retardancy expressed in g anhydrous ammonium bromide per 100 g fabric were about 6.64-7.81 %. The results obtained follow the free radical theory.